دور الأجهزة المركزية في الوقاية من الفساد ومكافحته في التشريع الجزائري - هناء ونيس; عبير ضريف (جامعة الوادي University of El Oued, 2025)
تعد ظاهرة الفساد من أبرز التحديات التي تعيق مسار التنمية في مختلف المجالات الاقتصادية والاجتماعية والسياسية سواء داخل المؤسسات العامة أو الخاصة بالنظر الى خطورة هذه الظاهرة سعت الجزائر الى مواجهتها من خلال وضع آليات قانونية عبر المصادقة على الاتفاقيات والمعاهدات الدولية المخصصة لمحاربة الفساد وكرست ذلك في القانون 06-01 الذي يعد الاطار التشريعي الأساسي لمكافحة الفساد في البلاد . لتعزيز فعالية هذه الآليات تم انشاء هيئات متخصصة أبرزها السلطة العليا للشفافية والوقاية من الفساد ومكافحته والديوان المركزي لقمع الفساد واللتان يضطلعان بدور محوري في تفعيل القوانين وتطبيقها على أرض الواقع. ورغم الجهود المبذولة، لا تزال الجزائر بحاجة الى تطوير الوسائل التقنية والإجرامية لضمان تطبيق أكثر فعالية للقانون و تحقيق الردع اللازم للحد من جرائم الفساد Corruption is one of the most significant challenges hindering development across various economic, social, and political sectors, both within public and private institutions. Given the seriousness of this phenomenon, Algeria has sought to address it by establishing legal mechanisms through the ratification of international conventions and treaties dedicated to combating corruption. This was enshrined in Law 06-01, which serves as the fundamental legislative framework for combating corruption in the country. To enhance the effectiveness of these mechanisms, specialized bodies were established, most notably the High Authority for Transparency, Prevention, and Combating Corruption and the Central Office for Combating Corruption, both of which play a pivotal role in activating and implementing the laws. Despite the efforts made, Algeria still needs to develop technical and legal means to ensure more effective law enforcement and achieve the necessary deterrence to reduce corruption offenses.
قانون أعمال